Head and neck cancer recurrence with limited mouth opening, radiation fibrosis and confirmed COVID-19 infection: approach to airway management - Shamim, Faisal; Sohaib, Muhammad; Shahid, Kashaf; Abbas, Syed Akbar (Journal of the Pakistan Medical Association, 2023)
We present a case that describes the airway management of a patient with recurrent head and neck cancer and confirmed COVID-19 infection. Securing airway of these patients with anticipated difficulty and at the same time limiting virus exposure to providers can be challenging. The risk of aerosolization during awake tracheal intubation is extreme as it carries a high risk of transmitting respiratory infections. A multidisciplinary team discussion before the procedure highlighted aspects of both airway management and the urgency of surgical procedure where particular care and modifications are required. Successful flexible bronchoscopy and intubation was done under inhalational anaesthetics with spontaneous breathing. Although fiberoptic intubation during sleep,in anticipated difficult airways, have led to enhanced intubation time, this technique was opted to minimize the risk of aerosol generation associated with topicalisation, coughing and hence reduced incidence of cross infection to health care workers.